An Investigation of the Relationship between Writing Achievement and Writing Strategy Use by Secondary School Students (Journal Of Educational and Psychological Researches, 2022)
Basically, this study aims to identify the extent to which Iraqi secondary school students use writing strategies and how proficiency level and students gender could affect writing strategy use. The study also examines the relationship between writing achievement and writing strategy use among Iraqi secondary school students. For this purpose, 140 Iraqi secondary school students were selected randomly from six different schools. Petric and Czarl’s questionnaire (2003) was adopted in the study as an instrument to collect the needed data. A software of SPSS used to analyze the collected data. The findings revealed that secondary school students appeared as low users of writing strategies; low proficient students do not show a statistically significant difference compared to high proficient students, female students use more strategies compared to male students do. The study also found a positive correlation between writing strategy use and writing achievement.